Implementation of the Sorogan Method in Understanding the Jurumiyah Book - Silfiyatul Jannah; Muhammad Nur Hadi; Muhammada Muhammada; Saifulah Saifulah (Community: Jurnal Hasil Penelitian dan Pengabdian Masyarakat, 2026)
This study aims to analyze the implementation of the sorogan method in learning the Book of Al-Jurumiyyah and to find out the development of students' understanding of nahwu material in Dormitory I of the Ngalah Sengonagung Purwosari Islamic Boarding School, Pasuruan. This research uses a qualitative approach with a case study type of research. Data collection techniques are carried out through observation, semi-structured interviews, and documentation. The results of the study show that the implementation of the sorogan method is carried out individually through the stages of material preparation, submission of readings, direct correction, and continuous evaluation. The students perform muthala'ah before depositing the reading to the ustadzah, then the ustadzah provides corrections to errors in harakat, meaning, and the application of nahwu rules. The application of the sorogan method has been proven to be able to improve the ability to read books without harakat, understanding the rules of nahwu, reading thoroughness, and the courage of students in explaining the material. The development of students' understanding shows diverse results according to their educational background, basic Arabic language skills, and the intensity of each student's practice, but in general the sorogan method is considered effective because it provides personalized, active, and intensive learning. Thus, the sorogan method remains relevant in learning the yellow book as an effort to strengthen basic Arabic language competencies and understanding of nahwu students in the pesantren environment.